2019
DOI: 10.4103/jfmpc.jfmpc_202_18
|View full text |Cite
|
Sign up to set email alerts
|

Myositis associated with Salmonella paratyphi A bacteremia appears to be common

Abstract: Background: Fever and severe myalgia in a tropical country like India bring to mind leptospirosis, rickettsioses, dengue, and other viral fevers. Enteric fever is widely prevalent in Asia, but myositis has not been previously described in Salmonella paratyphi A bacteremia. Materials and Methods: Retrospectively, we recruited patients with enteric fever admitted to our treating unit over a 6-month period. Demography, historical, clinical, and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Salmonella typhi has been reported to cause rhabdomyolysis and focal abscesses. 4 A study compared the clinical features of salmonella muscle infections with those who reported typical pyomyositis with staphylococcus aureus. The literature study was divided by sex, duration of symptoms at presentation, and muscle group involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella typhi has been reported to cause rhabdomyolysis and focal abscesses. 4 A study compared the clinical features of salmonella muscle infections with those who reported typical pyomyositis with staphylococcus aureus. The literature study was divided by sex, duration of symptoms at presentation, and muscle group involvement.…”
Section: Introductionmentioning
confidence: 99%